Information Sources Utilization Pattern among Tribal Fish Farmers - Pandey, D K; Upadhayay, A D; Datta, M K; Biswas, P (Fishery Technology, 2025)
Tribal fish farmers in the state of Tripura constitute about 40% of the total fish farmers populace and are potential stakeholders in the overall fish production. A study was undertaken in Tripura with a sample size of 90 tribal fish farmers, selected using stratified random sampling method. Demographic profile revealed that majority (52.22%) of them were from old age group with higher literacy rate, small land holdings, low income, medium extension participation and aspiration. Respondents indicated that television was the major (85.56%) mass media source for information. Amongst interpersonal localite sources, the Panchayat emerged as main source of information, while meeting and group discussions (62.23%) and demonstration (57.78%) were major interpersonal cosmopolite information sources. Information source utilization for 59% of the respondents was at medium level. Independent variables viz., income, extension participation and level of aspiration showed a positive and significant relation with utilization of communication channels. More proactive role on the part of line departments Krishi Vigyan Kendras and other information providers is emphasized in order to accelerate the usage of cosmopolite sources of information among the tribal community of the State.